2018
DOI: 10.1109/ted.2018.2817919
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Randomly Distributed Dopants on $\Omega$ -Gate Junctionless Silicon Nanowire Transistors

Abstract: This paper presents experimental and simulation analysis of an -shaped silicon junctionless nanowire field-effect transistor (JL-NWT) with gate lengths of 150 nm and diameter of the Si channel of 8 nm. Our experimental measurements reveal that the ON-currents up to 1.15 mA/μm for 1.0 V and 2.52 mA/μm for the 1.8-V gate overdrive with an OFF-current set at 100 nA/μm. Also, the experiment data reveal more than eight orders of magnitude ON-current to OFF-current ratios and an excellent subthreshold slope of 66 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…When the channel or gate lengths of a transistor are greatly larger than the mean-free-path of charge carriers, mobility is a meaningful index for devices in the drift-diffusion regime. Compared to a bulk material, the cross-sectional dimensions of a nanowire are reduced, which leads to different scattering effects to alter mobility. For instance, for the nanowires with diameters between strong quantum confinement and pure classical regimes, Das et al found that mobility fluctuates with increasing diameter ( d NW ) of nanowires, which originates from appeared new channels for interband scattering . Due to the distinct band splitting and modifying of nanowires with different crystal directions, anisotropic effects on mobility take place in nanowires.…”
Section: Fundamental Electronic Properties Of Single Nanowire Transis...mentioning
confidence: 99%
“…When the channel or gate lengths of a transistor are greatly larger than the mean-free-path of charge carriers, mobility is a meaningful index for devices in the drift-diffusion regime. Compared to a bulk material, the cross-sectional dimensions of a nanowire are reduced, which leads to different scattering effects to alter mobility. For instance, for the nanowires with diameters between strong quantum confinement and pure classical regimes, Das et al found that mobility fluctuates with increasing diameter ( d NW ) of nanowires, which originates from appeared new channels for interband scattering . Due to the distinct band splitting and modifying of nanowires with different crystal directions, anisotropic effects on mobility take place in nanowires.…”
Section: Fundamental Electronic Properties Of Single Nanowire Transis...mentioning
confidence: 99%
“…To prevent the disturbance of unphysical charge trapping and initiate further efforts to specify the nano-scale electronic devices with the short channel effect [29], the quantum mechanical effect was considered during the simulation of the NCJL-FinFET. The mobility model was incorporated with the high-field saturation and Shockley Read Hall physical model to accomplish the recombination and generation [30]. As a consequence of the time consumption of each randomization device, 200 randomization samples comprising varying doping profiles were reproduced.…”
Section: Simulation Scheme For Rdf Effectmentioning
confidence: 99%
“…In our previous work, we have shown an extensive comparison between simulations and experimental results for JL-NWTs with Ω-gated region and with a channel length of 150 nm [6]. In another study, we have discussed statistical simulation results based on an ensemble of 500 JL-NWTs, where each device is atomistically unique with random distribution of discreet dopants in the channels [7]. Results obtained from those previously reported works have allowed us to suggest an improvement of the device design, predict the device performance and to extract (FoM), such as OFF-current (IOFF) and ON-current (ION), subthreshold slope (SS) and voltage threshold (VTH).…”
Section: Introductionmentioning
confidence: 99%
“…In this letter, we would like to extend our previous works [6] [7] further and explore the opportunity to include multi-layer neural network (NN) in our analysis in order to predict device characteristics without running numerical TCAD device simulations. To the best of our knowledge this is the first paper that establishes a direct link between NN and TCAD simulations.…”
Section: Introductionmentioning
confidence: 99%